If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 45 = -29 Reorder the terms: 45 + x = -29 Solving 45 + x = -29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + x = -29 + -45 Combine like terms: 45 + -45 = 0 0 + x = -29 + -45 x = -29 + -45 Combine like terms: -29 + -45 = -74 x = -74 Simplifying x = -74
| h+7.74=7.2 | | 5x-9(x+1)+(5x-1-2)=9 | | -5/8-5/12= | | -6(n-2)=9-5n | | -3(4-3z)=4z+3 | | 5x+24-x=21 | | 6z-3=9z-4z | | x-4.5=-8.9 | | 8(3x-8)=2(12x+5) | | -22=32+m | | 14y-12y=4 | | -7/16+7/32= | | 3(b-4)-b=-8 | | x-32=17 | | xm+6m+8=0 | | 3t-9=23-t | | 7.4x+5.93=-22.93 | | (9u^3+8)-(14u^3-11)= | | 2y=-26 | | 3z+14=2z+1 | | 5x-(2x^2-4x)+9x^2= | | 4y+7=7 | | s=5n+5z | | x+31=-10 | | 3*4-4*-2+2= | | 18=2-(z+7) | | P=.5ab | | 2.3y=69 | | 7d+2(d+2)=16 | | 1.4x-2x-6=12 | | 3*-4-4*-2+2= | | -7t+9=-4(2t-3) |